MENGEMBANGKAN KREATIVITAS SISWA DENGAN JOYFUL LEARNING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 8 KOTA TASIKMALAYA - Sariduduin; Saridudin, Sariduduin (HASBUNA : Jurnal Pendidikan Islam, 2025)
Islamic Religious Education learning in some schools is sometimes less interesting for some students. The lack of student activity evidences this. They look less enthusiastic when participating in learning, less active, passive, and less responsive to learning taught by educators. The joyful learning model is one of the learning models designed in various ways to create a pleasant and exciting learning atmosphere to provide a more meaningful learning experience, especially in Islamic Religious Education learning, both inside and outside the classroom. This study aims to analyze how much the joyful learning model can improve student creativity in Islamic Religious Education at SMPN 8 Tasikmalaya City. This study was conducted with a descriptive qualitative approach by collecting data through interviews, observations, and documentation with data analysis techniques using Miles and Huberman's qualitative data analysis, which includes data collection, data reduction, presentation, and conclusions. The results of the study indicate that the joyful learning model can be a driver in fostering student learning creativity in Islamic Religious Education subjects, especially in the ability to recite, read, and memorize short letters in the Qur'an and increase numerical values ​​or develop student abilities with other works such as mind mapping and calligraphy.